2000
DOI: 10.1007/s004390000426
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Y chromosome haplotypes of Israeli and Palestinian Arabs reveal geographic substructure and substantial overlap with haplotypes of Jews

Abstract: High-resolution Y chromosome haplotype analysis was performed in 143 paternally unrelated Israeli and Palestinian Moslem Arabs (I&P Arabs) by screening for 11 binary polymorphisms and six microsatellite loci. Two frequent haplotypes were found among the 83 detected: the modal haplotype of the I&P Arabs (approximately 14%) was spread throughout the region, while its one-step microsatellite neighbor, the modal haplotype of the Galilee sample (approximately 8%), was mainly restricted to the north. Geographic subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 46 publications
6
49
1
Order By: Relevance
“…3,4,11 However, in a combined non-Ashkenazi sample of 320 individuals (Sephardic, Kurdish Jews and Palestinians), 4 H6 was found only in a single Sephardic Jew (0.3%; Figure 1). This finding strongly 5 (ranging from 0.89470.022 to 0.91970.026), and by the fact that in a combined Ashkenazi -European network, Jews present only a subset of the haplotypes (not shown).…”
Section: Resultsmentioning
confidence: 94%
“…3,4,11 However, in a combined non-Ashkenazi sample of 320 individuals (Sephardic, Kurdish Jews and Palestinians), 4 H6 was found only in a single Sephardic Jew (0.3%; Figure 1). This finding strongly 5 (ranging from 0.89470.022 to 0.91970.026), and by the fact that in a combined Ashkenazi -European network, Jews present only a subset of the haplotypes (not shown).…”
Section: Resultsmentioning
confidence: 94%
“…This hypothesis was confirmed in a recent study (ref. 17 and manuscript in preparation) in which the three haplogroups were further defined by five additional binary polymorphisms (M9, M13, M17, M20 and SRY10831). Our results showed that the long and short alleles of both DYS388 and DYS392 segregated almost completely between these newly defined haplogroups.…”
Section: Discussionmentioning
confidence: 99%
“…The haplogroup frequencies are presented in table 4. Because the set of markers screened in this study were not exactly the same as those screened in the published studies (Hammer et al 2000;Nebel et al 2000), some of the haplogroups could not be resolved and had to be pooled. It is seen that there is substantial overlap in the types of haplogroups observed in the north Indian and in the Middle Eastern regions.…”
Section: Footprints From Central and West Asiamentioning
confidence: 99%